The acoustics of racing engine intake systems - Harrison, M. F.; Dunkley, A. (Elsevier, 2004)
Naturally aspirated racing engines have tuned intake systems and can now achieve volumetric efficiencies in excess of 125% and peak engine speeds in excess of 18,000 rev/min. Engines designed for single seater racing commonly dispense with the intake manifold and its convoluted and restricting flow path preferring single lengths of pipe feeding each cylinder separately. An investigation into the intake process on a single cylinder racing engine has shown that inertial ram effects make a strong contribution to the intake process at high engine speeds whereas acoustic resonance effects are more important to the rather weak wave action that occurs at low engine speeds. An acoustic model of the resonant wave action has proved useful in distinguishing between these two effects. The attributes of the acoustic model have been compared to those of more traditional time-marching gas-dynamics calculation methods. A decoupled hybrid method has been shown to yield calculations of the wave dynamics in the intake system of a single cylinder racing engine that show fair agreement with measured results up to the 10th harmonic of the engine cycle frequency. In a case study, the intake characteristics of a single cylinder racing engine have been shown to differ only slightly from those expected from the V10 engine on which it is based, although this will only be the case when the dimensions of the intake system are chosen appropriately.